Etnobotani tumbuhan obat pada masyarakat Kampung Jamu Sumbersari Kelurahan Wonolopo Kecamatan Mijen Semarang - Fiakhsani Fiakhsani; Murningsih Murningsih; Jumari Jumari (Jurnal Biologi Tropika, 2020)
Kampung Jamu Sumbersari is an area in Wonolopo, Mijen District, Semarang City. The majority of the population produces herbal medicine and sells it themselves. This study aims to examine the diversity of medicinal plants; know the kinds of ingredients, ingredients composition, and utilization of medicinal plants; reviewing the provision of herbal ingredients to the people of Kampung Jamu Sumbersari. The research was conducted from April to May 2020 in the community of Jamu Sumbersari Village in Wonolopo Village, Mijen District, Semarang. The data collection method used participant observation and semi-structured interviews. The data analysis used qualitative and quantitative descriptive analysis techniques. The results showed that 27 types of plants used in herbal medicine are included in 16 families, with the family having the most widely used species is Zingiberaceae 8 species. There are 9 kinds of herbal concoctions with the composition of ingredients, methods of concoction and their use which are made to treat various diseases or as health care. The most part of the plant organs used for the concoction of herbal medicine is the leaves (26%). Most of the materials used as herbal ingredients are obtained by buying from the market or collectors, only a small part of the production itself. It is hoped that the benefits of the research carried out as a source of information regarding the types of medicinal plants, herbal concoctions, ingredients composition and utilization in the people of Kampung Jamu Sumbersari.